Modes and progression of tool deterioration and their effects on cutting force during end milling of 718plus Ni-based superalloy using cemented WC-Co tools - Nurul Hidayah, Razak (2017)
Understanding the detailed progression of cutting tool deterioration and how deterioration affects cutting force (F) during milling of difficult-to-cut Ni-based superalloys is important for the improvement of machinability of the alloys. It also serves to clarify whether and how an F-based method for monitoring tool deterioration is possible. This understanding is however far from sufficient, as is explained in this thesis after a comprehensive review of the literature. The aim of the present research is thus to determine and explain the modes and progression of tool deterioration and how cutting forces may vary due to the various deterioration features of the cutting tool edge.